Analysis of building behavior in construction industry and its relationship with its business performance for state contracting in Boyacá, Colombia - Hernández Carrillo, Carlos Gabriel; Gutiérrez Junco, Oscar Javier; Sarmiento Rojas, Jorge Andrés (Revista Venezolana de Gerencia, 2023)
Construction provides the infrastructure necessary for the progress of modern societies and responds favorably to global economic dynamics. This performance is conducted through business performance, when formulating and executing this type of projects in Colombia. However, Its productivity is low, despite its support as a leading stimulator of production in times of crisis. Therefore, this research analyzed the macroeconomic environment of the construction and building subsector, through the selection and characterization of companies in Boyacá, Colombia, together with the identification of their capacities, estimated by the financial and organizational statements required in public bids. This analysis exposes the dependent and volatile market, mainly supported by housing construction activity. In Colombia, there is a reduction in productivity and in Boyacá, 95.83% of sole proprietorships do not have conditions to participate in public procurement. Consequently, despite institutional efforts to encourage production by investment in the building subsector, the nature of the market and the organizational limitations hinder the development of the sector and the Colombian economy in times of crisis.